2022
DOI: 10.3389/fneur.2022.902402
|View full text |Cite
|
Sign up to set email alerts
|

Construction and validation of a glioblastoma prognostic model based on immune-related genes

Abstract: BackgroundGlioblastoma multiforme (GBM) is a common malignant brain tumor with high mortality. It is urgently necessary to develop a new treatment because traditional approaches have plateaued.PurposeHere, we identified an immune-related gene (IRG)-based prognostic signature to comprehensively define the prognosis of GBM.MethodsGlioblastoma samples were selected from the Chinese Glioma Genome Atlas (CGGA). We retrieved IRGs from the ImmPort data resource. Univariate Cox regression and LASSO Cox regression anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…This study shows that expression of cGAS-STING pathway members like STING, revealed that patients with PTEN mutation are in the highrisk group [21]. Increased immune cell infiltration, more aggressive immune activity, higher expression of immune checkpoint genes, and less benefit from immunotherapy are listed among the characteristic features of these high-risk group patients [21]. These results are also in accordance with the PTEN-associated immune prognostic signature in GBM [22,23].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This study shows that expression of cGAS-STING pathway members like STING, revealed that patients with PTEN mutation are in the highrisk group [21]. Increased immune cell infiltration, more aggressive immune activity, higher expression of immune checkpoint genes, and less benefit from immunotherapy are listed among the characteristic features of these high-risk group patients [21]. These results are also in accordance with the PTEN-associated immune prognostic signature in GBM [22,23].…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, mutation-dependent gain or loss of function of phosphatase activity might have potential effects on interferon release. This study shows that expression of cGAS-STING pathway members like STING, revealed that patients with PTEN mutation are in the highrisk group [21]. Increased immune cell infiltration, more aggressive immune activity, higher expression of immune checkpoint genes, and less benefit from immunotherapy are listed among the characteristic features of these high-risk group patients [21].…”
Section: Discussionmentioning
confidence: 73%
“…Studies have implicated MSH2, which plays a key role in DNA mismatch repair, as having a potential predictive role, 50 as well as immune-related genes. 51,52 Male glioblastoma patients have a lower OS compared with women. [53][54][55] A retrospective, secondary study utilizing data from NRG Oncology RTOG trials developed and independently validated prognostic nomograms which take sex into consideration.…”
Section: Nomogramsmentioning
confidence: 99%